A multiscale finite element method for soil-rock mixture - Liu, Jia; Feng, Deluan (Frontiers in Materials, 2023)
Soil-rock mixture is a complex multi-phase composite geotechnical material, and its strength is determined by the physical properties of internal multi-phase materials and their coupling mechanical response between different phases of materials. The classical elastic-plastic finite element method established on a single macro scale neglects the control mechanism of the soil-rock mixture on the micro scale, and cannot simulate and predict the deformation − failure process of the soil-rock mixture. Based on the Eshelby-Mori-Tanaka equivalent inclusion average stress principle, a concise calculation formula of multi-scale coupled shear strength of soil-rock mixture considering the interaction effect of rock block and soil is established, and the rotational degree of freedom reflecting the microscopic motion details of rock block is introduced. The multi-scale coupled elastoplastic constitutive relationship of soil-rock mixture is derived, and it is compiled into a multi-scale finite element program. Through the large-scale direct shear test of soil-rock mixture, the model parameters of the multi-scale finite element method are determined, and then the multi-scale finite element program is used to simulate and predict the cross-scale deformation process of the soil-rock mixture slope. The results show that the multi-scale finite element method can effectively describe the influence of the mechanism of the micro motion characteristics of the soil-rock mixture on the macro mechanical response, and can effectively overcome the pathological mesh-dependency of the classical elastoplastic finite element method; During the deformation of the soil-rock mixture slope, the rotation displacement of the rock block is mainly concentrated in the shear zone of the slope, and the rotation displacement of the rock block outside the shear zone is zero. The micro physical mechanism of the cross scale evolution of the shear band of the soil-rock mixture slope can be explained as follows: the rotation of the rock block weakens the strain transmission ability between the rock block and the matrix soil, thus forming the concentration and development of the plastic strain, and finally leading to the penetration of the shear bands of the slope and the overall sliding failure.